ProtEQ : Social-emotional Development Media for Gifted Children in Pre-schools - Sidqia, Tiara Lisania; Ramadhan, Fazlur; Yanti, Fuzi; Salsabila, Ia; Riyadhi, Muhammad Ilham; Kurniati, Euis (JURNAL PENDIDIKAN USIA DINI, 2024)
Gifted children are children who have high potential in various fields such as science, math, art, music, language, have creativity and task commitment. One of the challenges faced by gifted children is social-emotional problems, even though mature social development will help individuals interact well with other individuals. One of the efforts to overcome these problems is to develop media that easy to use and reach by various parties such as websites. Design and Development Research (D&D) from Ellis and Levy (2010) was chosen as the research method, data collection techniques were carried out through interviews and questionnaires with thematic analysis techniques and descriptive statistics. The participants involved were children, teachers, parents, media experts, and special education experts. The results showed that there are two main problems in gifted children, namely obstacles in interacting and obstacles in managing emotions. Based on this analysis, the website development is focused on three services, i.e.: 1) services for children; 2) services for parents; and 3) services for teachers. The developed website received a "very good" rating from the validator and also received a positive response from the research participants. Therefore, this website can be used as a medium for the social-emotional development of gifted.